Spectrophotometric Determination of Praseodymium by 1,4- Dihydroxyanthraquinone after its Selective Separation from Rosetta Monazite Rare Earth Concentrate by Solvent Extraction - Abdel Fattah N. A, Sadeek A. S, Ali B. H, Abdo, A. A, Weheish, H. L.a, (Arab Journal for Sciences and Research Publishing, 2015)
A rare earths concentrate of Rosetta monazite assays about 44, 23, 16.94 and 5.91 % for Ce, La, Nd and Pr respectively. Separation of cerium by air oxidation at 200oC. Selective separation of Pr by D2EHPA at pH1 followed by a sensitive spectrophotometric method which described for the determination of praseodymium (Pr) with l,4-dihydroxyanthraquinone . The calibration curve was linear from   0.1 to 12 µgml -1 praseodymium. The influences of various parameters and reaction conditions for maximum colour development were investigated. The relative standard deviation for determination of 1 µgml-1 praseodymium has found to be 1.3 after 5 repeated determinations; percent error 5.02%, molar absorptivity (ε) was 1.23x106M-1 cm-1and detection limit was 0.1µgml-1. The method for determination of praseodymium showed good accuracy and selectivity.
Keywords: Spectrophotometric; Determination; Praseodymium; Dihydroxyanthraquinone; Rosetta Monazite; Selective Separation